Development of a 3‐dimensional tissue lung phantom of a preterm infant for optical measurements of oxygen—Laser‐detector position considerations. Issue 3 (14th September 2017) - Larsson, Jim; Liao, Peilang; Lundin, Patrik; Krite Svanberg, Emilie; Swartling, Johannes; Lewander Xu, Märta; Bood, Joakim; Andersson‐Engels, Stefan
Abstract : There is a need to further improve the clinical care of our most vulnerable patients—preterm infants. Novel diagnostic and treatment tools facilitate such advances. Here, we evaluate a potential percutaneous optical monitoring tool to assess the oxygen and water vapor content in the lungs of preterm babies. The aim is to prepare for further clinical studies by gaining a detailed understanding of how the measured light intensity and gas absorption signal behave for different possible geometries of light delivery and receiver. Such an experimental evaluation is conducted for the first time utilizing a specially developed 3‐dimensional‐printed optical phantom based on a geometry model obtained from computer tomography images of the thorax (chest) of a 1700‐g premature infant. The measurements yield reliable signals for source–detector distances up to about 50 mm, with stronger gas absorption signals at long separations and positions related to the lower part of the lung, consistent with a larger relative volume of this. The limitations of this study include the omission of scattering tissue within the lungs and that similar optical properties are used for the wavelengths employed for the 2 gases, yielding no indication on the optimal wavelength pair to use. Abstract : Development of optical techniques in medical applications can be difficult due to limited access to realistic phantoms. In order to have a stable, lasting and realistic phantom for testing of optical techniques, a 3‐dimensional‐printed plastic phantom is created based on computer tomography images. It is printed so that the different component—that is, bone, heart, fat and skin—can be filled with a liquid phantom with known absorption and scattering properties.